2007
DOI: 10.1002/cncr.23162
|View full text |Cite
|
Sign up to set email alerts
|

Multiple biomarkers improve prediction of bladder cancer recurrence and mortality in patients undergoing cystectomy

Abstract: BACKGROUND.Tested was whether the assessment of 5 established bladder cancer biomarkers (p53, pRB, p21, p27, and cyclin E1) could improve the ability to predict disease recurrence and cancer‐specific survival after radical cystectomy in patients with pTa‐3N0M0 urothelial carcinoma of the bladder (UCB).METHODS.The study comprised 191 patients with pTa‐3N0M0 UCB treated with radical cystectomy and bilateral lymphadenectomy (median follow‐up, 3.1 years). Biomarker expression was assayed on serial tissue microarra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
132
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 183 publications
(139 citation statements)
references
References 42 publications
5
132
1
1
Order By: Relevance
“…Clearly there is a subset of patients with pathologic T 2 and node-negative disease who have occult metastasis at the time of surgery and may derive benefit from adjuvant chemotherapy. To this end, enrollment in trials such as the p53 trial, which tested the utility of adjuvant chemotherapy in patients with organ-confined (pT 1 -T 2 ) high-risk UCB based on p53 status, is strongly recommended as molecular stratification, pharmacogenetics, and/or improved imaging modalities will be necessary to tailor adjuvant therapy for these patients (22).…”
Section: Discussionmentioning
confidence: 99%
“…Clearly there is a subset of patients with pathologic T 2 and node-negative disease who have occult metastasis at the time of surgery and may derive benefit from adjuvant chemotherapy. To this end, enrollment in trials such as the p53 trial, which tested the utility of adjuvant chemotherapy in patients with organ-confined (pT 1 -T 2 ) high-risk UCB based on p53 status, is strongly recommended as molecular stratification, pharmacogenetics, and/or improved imaging modalities will be necessary to tailor adjuvant therapy for these patients (22).…”
Section: Discussionmentioning
confidence: 99%
“…29 Similarly, Shariat and colleagues demonstrated that the addition of altered cell cycle biomarkers increased the predictive accuracy of nomogram-based disease recurrence and disease-specific survival by 10%. 30 Finally, improved characterization of the molecular pathways driving bladder cancer resulted in the identification of disease biomarkers that suggest the following therapeutic angles: mutations of fibroblast growth factor receptor 3 tyrosine kinase receptor are associated with superficial bladder cancer and a promising target for novel therapies. 38 The epidermal growth factor receptor (EGFR) pathway, associated with invasion and poor prognosis, may Advanced urothelial cancer be targeted with EGFR-family tyrosine kinase inhibitors.…”
Section: Biomarkers Of Prognosis and Therapeutic Efficacymentioning
confidence: 99%
“…Biomarkers that enhance the predictive ability of standard clinicopathologic information and optimize prognostication are being discovered. [19][20][21][22][23][24][25][26][27][28][29][30] In addition, advanced technologies offer a systematic approach for identifying active targets for drug discovery and tailored therapeutics in bladder cancer. The method described here defines a "personalized selection" approach to advanced bladder cancer within this increasingly tailored diagnostic and therapeutic framework, since optimizing management of a patient's This review explores recent advances laying the groundwork toward making "personalized selection" a reality for patients with muscle invasive and metastatic bladder cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The cell cycle regulators, p53, retinoblastoma protein, p21, p27 and cyclin E1, have been reported to predict disease recurrence and mortality following radical cystectomy in patients with pTa-pT3 node-negative UCC (12). A combination of these markers exhibited significantly higher predictive accuracy for disease recurrence and cancer specific mortality compared with isolated use of the markers; however, the use of individual markers did not improve the predictive accuracy (12)(13)(14). Therefore, the identification of a novel marker that predicts survival of patients with aggressive UCC more accurately is urgently required.…”
Section: Introductionmentioning
confidence: 99%